Adenylation Activity of Carboxylic Acid Reductases Enables the Synthesis of Amides. (13th October 2017) - Wood, Alexander J. L.; Weise, Nicholas J.; Frampton, Joseph D.; Dunstan, Mark S.; Hollas, Michael A.; Derrington, Sasha R.; Lloyd, Richard C.; Quaglia, Daniela; Parmeggiani, Fabio; Leys, David; Turner, Nicholas J.; Flitsch, Sabine L.
Abstract: Carboxylic acid reductases (CARs) catalyze the reduction of a broad range of carboxylic acids to aldehydes using the cofactors adenosine triphosphate and nicotinamide adenine dinucleotide phosphate, and have become attractive biocatalysts for organic synthesis. Mechanistic understanding of CARs was used to expand reaction scope, generating biocatalysts for amide bond formation from carboxylic acid and amine. CARs demonstrated amidation activity for various acids and amines. Optimization of reaction conditions, with respect to pH and temperature, allowed for the synthesis of the anticonvulsant ilepcimide with up to 96 % conversion. Mechanistic studies using site‐directed mutagenesis suggest that, following initial enzymatic adenylation of substrates, amidation of the carboxylic acid proceeds by direct reaction of the acyl adenylate with amine nucleophiles.